Someone has to fail : the zero-sum game of public schooling - Labaree, David F., 1947- (Harvard University Press, 2010)
"What do we really want from schools? Only everything, in all its contradictions. Most of all, we want access and opportunity for all children--but all possible advantages for our own. So argues historian David Labaree in this provocative look at the way 'this archetype of dysfunction works so well at what we want it to do even as it evades what we explicitly ask it to do.' Ever since the common school movement of the nineteenth century, mass schooling has been seen as an essential solution to great social problems. Yet as wave after wave of reform movements have shown, schools are extremely difficult to change. Labaree shows how the very organization of the locally controlled, administratively limited school system makes reform difficult. At the same time, he argues, the choices of educational consumers have always overwhelmed top-down efforts at school reform. Individual families seek to use schools for their own purposes--to pursue social opportunity, if they need it, and to preserve social advantage, if they have it. In principle, we want the best for all children. In practice, we want the best for our own. Provocative, unflinching, wry, Someone Has to Fail looks at the way that unintended consequences of consumer choices have created an extraordinarily resilient educational system, perpetually expanding, perpetually unequal, constantly being reformed, and never changing much"--Publisher description